PENGEMBANGAN MEDIA MONOPOLI INOVATIF (MEMOTIF) TERHADAP HASIL BELAJAR SISWA KELAS III SEKOLAH DASAR - Hidayati, Fitri Dhotul; Rahmawati, Ery; Achmad Budi Susilo, Tri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2023)
Based on observations and interviews conducted by researchers in class III of SDN Pucang 4 Sidoarjo, it was stated that the low grades of students were caused by the students' lack of willingness to learn. The aim of this research is to determine the feasibility of developing innovative monopoly media (MEMOTIF) in learning, student activities when using innovative monopoly media (MEMOTIF), and student learning outcomes after using innovative monopoly media (MEMOTIF). The research method used is a development of Brog and Gall modified by (Sugiyono, 2016). The subjects of this research were 15 class III students at SDN Pucang 4 Sidoarjo. Techniques and data collection use expert validation, observation sheets, and tests. The results of this research obtained media validation with a percentage of 88% in the very appropriate category, material validation with a percentage of 94% in the very appropriate category, the results of student activities received a percentage of 87% in the very good category, and student learning outcomes experienced an increase from previously completing the pretest question scores. obtained a percentage of 33.33% in the poor category and the posttest completion score obtained a percentage of 86% in the very good category. Therefore, it can be concluded that the development of innovative monopoly media (MEMOTIF) can improve the learning outcomes of third grade elementary school students.